Effects of spatial scale on the built environments of community life circles providing health functions and services - Liu, Wenping; Zheng, Shuwen; Hu, Xuyu; Wu, Zhiqing; Chen, Shuaipeng; Huang, Ziqiu; Zhang, Wenting (Building and environment, 2022)
The built environment surrounding communities plays an important role in maintaining resident physical and mental health and social interaction. However, although this topic has received increasing attention in recent years, its effects at different spatial scales are still poorly understood. In order to meet the daily needs of community residents at different spatial scales, the community life circle is proposed as a new concept, which is a basic unit to meet the needs of residents’ life within the scope of daily walking. This study evaluated the potential health functions and services of the built environment surrounding a community at different spatial scales in the central district of Wuhan, China. Three scales of community life circles at 5-min, 10-min and 15-min, were selected for this analysis; physical, mental and social health were evaluated at the different scales. The results show that the built environment of community life circles at a large scale can provide more social health functions, while the built environment of community life circles at a small scale can promote the physical and mental health of residents. High-level health functions of the built environment, ranked in the top 30% of all communities, are mainly concentrated around large blue and green spaces, while high-level health services are more mainly concentrated in the urban center. Moreover, lower level health functions are more easily transformed into higher level health services in large-scale built environments. However, when the scale of the built environment increases from small to large, the increase in the high level of health functions at a small scale gradually decreases with scale and even becomes negative when exceeding the bottom 30% of the value. Our findings may help policy-makers better understand the effects of health functions and services of the built environment at different scales of community life circles, which may help promote health equity in urban communities. •Health functions and health services provided by built environments surrounding the community have different scale effects.•Built environments at a large scale can provide more social health functions.•The small-scale built environment is conducive to promoting physical and mental health.•Lower level health functions are more easily transformed into higher level services in large-scale built environments.•The high health functions that communities obtain in small-scale built environments are diminished in large scale.